PENGARUH KETERAMPILAN PROSES BERBASIS LABORATORIUM IPA TERHADAP HASIL BELAJAR SISWA MATERI USAHA DI SMP - Dewi, Lazaro Kumala; Tandililing, Edy; Mursyid, Syukran (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aimed to determine the effect of skill process of science laboratory based approach towards the student’s learning outcomes in Usaha (Work) material in SMP Negeri 11 Pontianak.this research was conducted through a pre-experimental design with one pretest and posttest group. The sample of this study was the students of class VIII F (N = 34) who were selected with intac group technique. In collecting the data, the researcher used measurement and observation technique. The instrument for collecting data were measurement test and observation checklist. The analysis shows that the average score of students is increased into 79,91 with the percentage of completeness is 85,3% after applying the skill process of science laboratory based approach. The data analysis was obtained by simple linear regression test that shows tcount 5,987 > ttable 2,037. Based on calculation, it shows that the effect size of this study was 2.9 which is classified as high criteria. This research is expected to be carried out to improve students learning outcomes. Keywords:   Skill Process Approach, Utillization of Science Laboratory, Learning Outcomes, Effect Size.